If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 1) + 17 = 0 Reorder the terms: 3(1 + x) + 17 = 0 (1 * 3 + x * 3) + 17 = 0 (3 + 3x) + 17 = 0 Reorder the terms: 3 + 17 + 3x = 0 Combine like terms: 3 + 17 = 20 20 + 3x = 0 Solving 20 + 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + 3x = 0 + -20 Combine like terms: 20 + -20 = 0 0 + 3x = 0 + -20 3x = 0 + -20 Combine like terms: 0 + -20 = -20 3x = -20 Divide each side by '3'. x = -6.666666667 Simplifying x = -6.666666667
| xy+x+y=x^2y^2 | | X^2+14x+2=-46 | | 4(x+3)+17= | | 2x+-1=49 | | 2x(7x-3)(x+4)=0 | | Z^2-11z=28 | | 12x-5y=20 | | 2x-1=49 | | 2(x+2)+24= | | x+5=x-1 | | -8x+4+9x=-1+7 | | 4(x+1)+21= | | 3(3x+1)+6(x-3)= | | 4y-4+y+20=5y+20-2y | | -4-x=6x-6 | | 8(x+3)=16x-4 | | -4r+5=-4r | | 3x+9=4x+6 | | 9x+4=85 | | B^2+9b=0 | | 0=x^3-9x-9 | | 2b-3=3b+1 | | 9t-5.8=-4.6+8.7t | | 5s-15=-11+6s | | x+12.5=17 | | -2(3x-5)=-14 | | 12v+6=18-48-9v | | Tc=3q^2+48q+3 | | 25-3a=3a+1 | | 75=5(k+3) | | 3x^3-15x^2-2x+10=0 | | 7a+12=68 |